PENERAPAN METODE A-STAR (A*) PADA PENENTUAN JARAK TERPENDEK KE FASKES APOTEK BPJS DI SURAKARTA - Defan Sumarsono Putra; Paulus Harsadi; Kumaratih Sandradewi (Universitas Katolik Musi Charitas, 2023)
A pharmacy is a place to sell and sometimes make or mix drugs. The pharmacy is also a place where pharmacists practice the pharmacy profession as well as become a retailer. However, not all pharmacies in Surakarta cooperate with Badan Penyelenggar`a Jaminan Sosial (BPJS). To help BPJS participant patients go faster to the pharmacy or pharmacy referrals and redeem drugs prescribed by doctors. By utilizing information technology the user can open an application in which there is a place to go and the determination of the path to be traversed. With the application using the A-Star (A*) method, the user will find it easier to choose the route to be taken and quickly arrive at the destination.The system that has been made has a comparison with the system that is running now namely google maps and obtained an accuracy rate of 98,8% which can be given very well because it has an error value <10%.